Media Concentration in Spain: National, sectorial, and regional groups - Juan Pablo Artero-Muñoz; Ricardo Zugasti; Sira Hernánez-Corchete (Estudios sobre el Mensaje Periodístico, 2021)
In Spain, the media market structure is made up of very different media groups, making it necessary to identify and classify them in a clear and coherent manner. To do so, this article collects secondary information from media companies’ websites and from audience measurement institutions. Results identify 50 media groups with activity in the Spanish market. They are classified into three categories according to the type of outlet, including national, sectorial, and regional. The current structure is based on recent developments in the last four decades of democracy among newspapers, magazines, radio, television and digital media.